Hamstring Muscle Flexibility and Dynamic Balance in Elderly Residents of Bagendang Hulu Village: A Cross-Sectional Study - Maulidya, Maulidya; Saraswati, Putu Ayu Sita; Sugiritama, I Wayan; Putra, I Putu Yudi Pramana (Majalah Ilmiah Fisioterapi Indonesia, 2024)
Introduction : Aging brings about notable changes in the musculoskeletal system, affecting muscle flexibility and dynamic balance among the elderly. This study explores the correlation between hamstring muscle flexibility and dynamic balance in elderly residents of Bagendang Hulu Village, Central Kalimantan. Decreasing flexibility with age can lead to stiffness and reduced mobility, impacting daily activities. Hamstring muscles, crucial for tasks like standing and walking, contribute significantly to balance, despite their decreased flexibility in older adults. Dynamic balance, essential for mobility and fall prevention, integrates sensory, motor, and cognitive functions, influenced by muscle strength and joint functionality. Method : This cross-sectional study involved 66 participants aged 60-94 years from Elderly Integrated Health Posts. Hamstring flexibility was assessed using the Chair Sit and Reach Test, and dynamic balance was measured with the Timed Up and Go Test. Results : The study found no significant correlation (p > 0.05) between hamstring muscle flexibility and dynamic balance in this population. Conclusion : Active engagement in senior gymnastics is recommended to enhance physical fitness and overall quality of life, addressing factors such as cardiovascular health, hypertension risk, blood sugar regulation, flexibility, and balance maintenance. Future research should focus on larger sample sizes, controlling for medical histories, and balancing participant demographics to provide deeper insights. Understanding these relationships can inform interventions aimed at enhancing musculoskeletal health and reducing fall risks among elderly populations.   Keywords : Aging, hamstring muscle flexibility, dynamic balance, elderly, physical activity